Key Factors Dictating Excessive Lighting Energy Consumption in Schools: a Post-Occupancy Analysis - Peter Raynham; Roderic Bunn (Journal of Sustainable Design and Applied Research in Innovative Engineering of the Built Environment, 2017)
Good practice in lighting energy consumption in schools is regarded to be around 13 kWh/m2 per annum (CIBSE LG5, 2011). However, recent post-occupancy evaluations reveal lighting energy consumption in schools to be above 30kWh/m2 p.a., despite the use of energy efficient lamps, switching based on infrared presence/absence detection, and digital controls for daylight-linked dimming. To identify causes of excess energy consumption for lighting, this study undertook detailed post-occupancy field measurements of the lighting consumption of two recently-completed K schools – a small primary and a large secondary – equipped with digitally-addressable lighting interface (DALI) systems. Instrumentation of individual light fittings was carried out to obtain an accurate understanding of their switching and dimming characteristics. Results were compared with estimates of kilowatt hours per square metre per year (the Lighting Energy Numeric Indicator), calculated using the spreadsheet provided to support the European Standard that defines LENI, and against estimates of disaggregated whole-building energy consumption using the CIBSE energy assessment tool TM22. The post-occupancy evaluations uncovered excessive lighting consumption in classrooms and circulation area lighting, issues with DALI system installation and commissioning, and problems with the usability of lighting controls. Allied shortcomings included dysfunctional energy metering, lack of system fine-tuning after handover, and inaccuracies with as-built records. Methodological shortcomings were identified with the industry-standard methods of assessing lighting consumption. Recommendations are given on ways to mitigate excessive lighting energy consumption and to improve the predictive power of the current energy assessment methods.